The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.24130/eccd-jecs.1967202152295
|View full text |Cite
|
Sign up to set email alerts
|

STEM etkinliklerinin okul öncesi öğrencilerinin yaratıcı düşünmesine etkisi

Abstract: Bu çalışmanın amacı, okul öncesi eğitimi 5-6 yaş grubu öğrencilerine yönelik mühendislik tasarıma dayalı STEM etkinlikleri geliştirmek ve bu STEM etkinliklerinin öğrencilerin yaratıcı düşünmesine etkisini tespit etmektir. Araştırmada yöntem yarı deneysel desen benimsenmiştir. Araştırmanın çalışma grubunu, 5-6 yaş grubu sınıflarında öğrenim gören deney grubu ve kontrol grubu olmak üzere toplam 60 öğrenci oluşturmaktadır. Çalışmada 6 STEM etkinliği geliştirilmiş, her bir etkinlik toplam 8 haftalık süreçte uygula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…In a way that satisfies this sense of curiosity, robotic applications, coding and STEM activities for children will both enable children to explore their surroundings and support their active structure [52,54,100,101]. In the researches, it has been concluded that electronic books, STEM activities, augmented reality applications, robotic coding and applications applied for children in early childhood have a significant contribution to the development of creativity skills in children [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a way that satisfies this sense of curiosity, robotic applications, coding and STEM activities for children will both enable children to explore their surroundings and support their active structure [52,54,100,101]. In the researches, it has been concluded that electronic books, STEM activities, augmented reality applications, robotic coding and applications applied for children in early childhood have a significant contribution to the development of creativity skills in children [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the research, it was concluded that there was a significant increase in children's creativity skills. Another similar study was carried out by Güldemir and Çınar [59]. The researchers worked with 60 children from the age group of five-six for 8 weeks, accompanied by six STEM activities.…”
Section: Technology-creativity Relationship In Early Childhoodmentioning
confidence: 97%
“…Okul öncesi eğitimde STEM'i oluşturan disiplinlerin ve STEM deneyimlerinin çocukların gelişim düzeylerine uygun bir şekilde ele alınması gerekmektedir (Erol & İvrendi, 2021). Yapılan çalışmalar erken çocukluk döneminde çocukların STEM eğitiminden bilimsel süreç becerilerini (Ünal & Aksüt, 2021) ve yaratıcı düşünme düzeylerini olumlu etkilediğini ortaya koymuştur (Güldemir & Çınar, 2021). Bu nedenle bu çalışmada ortaya çıkan erken STEM eğitiminin gerekliliği bulgusunun alanyazınla desteklendiği görülmüştür.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Literatürde STEM ve STEAM eğitimlerinin çocukların, akademik benlik algıları (Koç, 2019) üzerinde de etkili olduğu saptanmıştır. Ayrıca, STEM eğitiminin çocukların, problem çözme becerilerini (Akçay-Malcok ve Ceylan 2021; Bal, 2018), bilimsel süreç becerilerini (Alan, 2020;Çilengir-Gültekin, 2019;Kavak, 2020) yaratıcılıklarını (Çilengir-Gültekin, 2019Güldemir, 2019;Üret, 2019) desteklediğini ortaya koymuştur. STEAM eğiminin çocukların birçok becerisinde etkililiğin ortaya konmasıyla söz konusu eğitiminde çocukları okula hazırlama noktasında yararlanma fikri düşülmeye başlanmıştır (Erol, 2021: 64).…”
Section: Steam Eğitimiunclassified